2002
DOI: 10.1142/s0218271802003031
|View full text |Cite
|
Sign up to set email alerts
|

On the Spin of Gravitational Bosons

Abstract: We unearth spacetime structure of massive vector bosons, gravitinos, and gravitons. While the curvatures associated with these particles carry a definite spin, the underlying potentials cannot be, and should not be, interpreted as single spin objects. For instance, we predict that a spin measurement in the rest frame of a massive gravitino will yield the result 3/2 with probability one half, and 1/2 with probability one half. The simplest scenario leaves the Riemannian curvature unaltered; thus avoiding confli… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(36 citation statements)
references
References 38 publications
1
35
0
Order By: Relevance
“…The (1, 0)⊕(0, 1) sector is well known and has been frequently elaborated in the literature, listed among others in [23], [16]. We here present it in the momentum space, and denote it by, B…”
Section: The Anti-symmetric Lorentz Tensor Spinor Of Second Rankmentioning
confidence: 99%
“…The (1, 0)⊕(0, 1) sector is well known and has been frequently elaborated in the literature, listed among others in [23], [16]. We here present it in the momentum space, and denote it by, B…”
Section: The Anti-symmetric Lorentz Tensor Spinor Of Second Rankmentioning
confidence: 99%
“…[35,36,37], have exposed the fact that the arguments advocated in Refs. [33,34] clearly assuming that the underlying spacetime be classical (or at least commutative). The studies reported in Refs.…”
Section: Main Features Of Dsr2mentioning
confidence: 99%
“…In the current section we consider massless four-vectors as direct products of Weyl spinors and co-spinors, an approach inspired by [11], [12] where the massive four-vectors have been described in terms of direct products of massive left-and right-handed spinors. For that purpose we begin by calculating χ⊗ τ , ρ ⊗ φ, χ⊗ φ and ρ ⊗ τ .…”
Section: Massless (1/2 1/2) Polarization Vectorsmentioning
confidence: 99%
“…Put another way, this means that (−iA 2 ) = e z transforms according to a trivial representation. In this way the massless (1/2, 1/2) representation of the Lorentz group, in contrast to the massive one [11], [12], is not irreducible but splits into a trivial representation, i.e. an so(1, 2) singlet, defined by the constant vector, (−iA 2 ) = e z , coinciding with the unit vector of the z axis, on one side, and an so(1, 2) triplet constituted by the two vectors, (−iA 1 ) = ǫ 1,1 , and (−iA 3 ) = ǫ 1,−1 , of negative norms, and time-like vector (−iA 4 ) = ǫ 1,0 ≡ n of a positive norm, on the other.…”
Section: Classification Of the Massless Four-vectors By The Casimir Imentioning
confidence: 99%